2012
DOI: 10.1007/s00216-012-5962-2
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted headspace solid-phase microextraction to quantify polycyclic aromatic hydrocarbons in pine trees

Abstract: A methodology for the extraction and quantification of 16 polycyclic aromatic hydrocarbons (PAHs) based on microwave-assisted extraction coupled with headspace solid-phase microextraction followed by gas chromatography/mass spectroscopy was validated for needles and bark of two pine species (Pinus pinaster Ait. and Pinus pinea L.). The limits of detection were below 0.92 ng g(-1) (dry weight) for needles and below 0.43 ng g(-1) (dw) for bark. Recovery assays were performed with two sample masses spiked at thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…Moreover, leaves of S. nigra collect a higher proportion of HMW PAHs than bark (33.8% vs. 23.6%), and bark captures a higher proportion of LMW PAHs than leaves (18.7% vs. 9.7%). This is opposite to that observed in the work of Ratola et al ( 2012 ) on the use of needles and barks of two pine species ( Pinus pinaster Ait. and Pinus pinea L.) as biomonitors, which showed that LMW PAHs are predominant in needles, while HMW PAHs are predominant in bark.…”
Section: Resultscontrasting
confidence: 96%
See 1 more Smart Citation
“…Moreover, leaves of S. nigra collect a higher proportion of HMW PAHs than bark (33.8% vs. 23.6%), and bark captures a higher proportion of LMW PAHs than leaves (18.7% vs. 9.7%). This is opposite to that observed in the work of Ratola et al ( 2012 ) on the use of needles and barks of two pine species ( Pinus pinaster Ait. and Pinus pinea L.) as biomonitors, which showed that LMW PAHs are predominant in needles, while HMW PAHs are predominant in bark.…”
Section: Resultscontrasting
confidence: 96%
“…Accumulation of PAHs on vegetative parts is plant species dependent, mainly to the chemical, morphological and physiological characteristics of each tree species (Fellet et al, 2016 ; Pereira et al, 2019 ; Rodriguez et al, 2012 ). The vegetative parts of a same tree species have also shown to have different abilities to accumulate PAHs (Ratola et al, 2009 , 2012 ; Yin et al, 2011 ). Identification of tree species, and different vegetative parts of a same tree species, with the best ability to accumulate air pollutants is still poorly known and constitutes an important research topic, mainly because data can allow to choose the most appropriate for a specific purpose and can also help to identify which factors control the PAH accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding PAHs extraction, ultrasonic extraction [ 11 , 18 , 20 ], Soxhlet extraction [ 18 , 21 , 23 ], accelerated solvent extraction [ 18 , 22 , 24 ], and microwave-assisted extraction [ 11 , 25 ] are the most used techniques, which involve the use of different organic solvents for better yields.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding pre-concentration, the rotary evaporator [ 17 ] and the nitrogen stream [ 32 ] are the common techniques used. For instrumental analysis, gas chromatography coupled to mass spectrometry (GC-MS) is the most widely used equipment for the detection and quantification of PAHs [ 14 , 22 , 23 , 24 , 25 , 33 ]. High-performance liquid chromatography with diode array (HPLC-DAD) and/or fluorescence detectors (HPLC-Fl) is another technique used, although to a lesser extent than GC-MS [ 20 , 21 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chemoecological importance of Pinus species has motivated a continuous interest for developing methods devoted to the determination of inorganic [14,15] and organic [16][17][18] pollutants. Remarkably, the great variability of climates and microclimates where the Pinus species grow, as well as the appearance of a wide range of morphological, chemical, and biochemical characters, has complicated the delimitation of the different species and the establishment of their taxonomic relationships [19][20][21].…”
Section: Introductionmentioning
confidence: 99%